Emergence of Epidemic Dengue-1 Virus in the Southern Province of Sri Lanka. - Champica K Bodinayake; L Gayani Tillekeratne; Ajith Nagahawatte; Vasantha Devasiri; Wasantha Kodikara Arachichi; John J Strouse; October M Sessions; Ruvini Kurukulasooriya; Anna Uehara; Shiqin Howe; Xin Mei Ong; Sharon Tan; et al. (Public Library of Science (PLoS), 2016)
BACKGROUND:Dengue is a frequent cause of acute febrile illness with an expanding global distribution. Since the 1960s, dengue in Sri Lanka has been documented primarily along the heavily urbanized western coast with periodic shifting of serotypes. Outbreaks from 2005-2008 were attributed to a new clade of DENV-3 and more recently to a newly introduced genotype of DENV-1. In 2007, we conducted etiologic surveillance of acute febrile illness in the Southern Province and confirmed dengue in only 6.3% of febrile patients, with no cases of DENV-1 identified. To re-evaluate the importance of dengue as an etiology of acute febrile illness in this region, we renewed fever surveillance in the Southern Province to newly identify and characterize dengue. METHODOLOGY/PRINCIPAL FINDINGS:A cross-sectional surveillance study was conducted at the largest tertiary care hospital in the Southern Province from 2012-2013. A total of 976 patients hospitalized with acute undifferentiated fever were enrolled, with 64.3% male and 31.4% children. Convalescent blood samples were collected from 877 (89.6%). Dengue virus isolation, dengue RT-PCR, and paired IgG ELISA were performed. Acute dengue was confirmed as the etiology for 388 (39.8%) of 976 hospitalizations, with most cases (291, 75.0%) confirmed virologically and by multiple methods. Among 351 cases of virologically confirmed dengue, 320 (91.2%) were due to DENV-1. Acute dengue was associated with self-reported rural residence, travel, and months having greatest rainfall. Sequencing of selected dengue viruses revealed that sequences were most closely related to those described from China and Southeast Asia, not nearby India. CONCLUSIONS/SIGNIFICANCE:We describe the first epidemic of DENV-1 in the Southern Province of Sri Lanka in a population known to be susceptible to this serotype because of prior study. Dengue accounted for 40% of acute febrile illnesses in the current study. The emergence of DENV-1 as the foremost serotype in this densely populated but agrarian population highlights the changing epidemiology of dengue and the need for continued surveillance and prevention.